Perceiving party supports and attributes of Perikatan Nasional and Pakatan Harapan - Syed Abdullah Idid, Syed Arabi; Tengku Azzman, Tengku Siti Aisha (2021)
This study is on how Malaysians perceive the image of two main political parties, namely Pakatan Harapan (PH), the party that formed the government from 2018 to 2020 and Perikatan Nasional (PN), the current governing party. Both are coalition parties. PH is a component party of DAP, PKR and Amanah while Perikatan Nasional houses BERSATU, PAS and STAR. The Pakatan Harapan government in 2018 lost its majority in February 2020 with the withdrawal of BERSATU which, then began the government with support from PAS, GPS, STAR and UMNO. The Yang di-Pertuan Agong appointed Tan Sri Muhyiddin Yassin as the Prime Minister based on the premise that he enjoyed the confidence of members of parliament on March 1, 2020. This study takes the multitude concept of Image in studying two political parties, which departs from the ordinary focus of learning candidates or politicians. Scholars studying candidate Images were keen to know which attributes appeal to which segment of the voters. Some voters may perceive a candidate as religious to be associated with such a character. In contrast, others may prefer the quality of a candidate who is educated or communally aspired. The present study, conducted in July 2020, interviewed some 820 respondents face-to-face nationwide to understand voter perception of the two parties. The questionnaire included questions on political beliefs, media use, and voting behaviour. This presentation will only analyse party attributes. Respondents gave their agreement on a total of 13 party attributes which provided a composite picture of the political party they had in mind. The findings found PN to have a better image than PH, and the difference held was significant. PH had a more favourable impression than PN among the Chinese and Indians, and PN is more favourable among Malays. Generally, Malaysians perceived PN to be championing their cause, willing to listen to problems and had a good set of leaders compared to the same attributes for PH. The Malays perceived PN to be more positive as a party to champion their community and religion, while the Chinese and Indians regarded the same attributes to be more forthcoming from PH. Older adults had a more favourable impression of PN and PH is more favourable among young